2021
DOI: 10.1590/0103-8478cr20200353
|View full text |Cite
|
Sign up to set email alerts
|

Producers’ access to agricultural credit in Turkey: the case of Adana province

Abstract: The issue of producers’ access to agricultural credit is the key word in contemporary debates in the sense that this theme is increasingly addressed at conferences and scientific congresses. This is explained by the fact that agricultural credit is today considered as an important key to the development of the agricultural sector in developing countries. This study examined the factors influencing producers’ access to agricultural credit in Turkey, precisely in the province of Adana. Questionnaire-based survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…The aging of the rural population in Poland analyses the concept of the silver economy as a new model for the development of rural areas and the problems associated with it, and provides an opportunity for sustainable rural development (Krzyminiewska G, 2019) [ 23 ]. In the context of accelerated ageing of the rural population, global agricultural production is threatened by a number of factors, the most common of which are climate change and the prevalent problem of declining soil fertility, inferring that any factor affecting the rural population has an impact on agricultural production (Akdemir S, Miassi Y, 2020) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aging of the rural population in Poland analyses the concept of the silver economy as a new model for the development of rural areas and the problems associated with it, and provides an opportunity for sustainable rural development (Krzyminiewska G, 2019) [ 23 ]. In the context of accelerated ageing of the rural population, global agricultural production is threatened by a number of factors, the most common of which are climate change and the prevalent problem of declining soil fertility, inferring that any factor affecting the rural population has an impact on agricultural production (Akdemir S, Miassi Y, 2020) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the desire for formal credit was positively and substantially impacted by formal education, agricultural experience, and the size of landholdings, road access, and extension connections. Akdemir et al (2021) looked at the determinants affecting farmers' access to agricultural loans in the region of Adana, Turkey. A sample of 101 producers who had received training in basic random was subjected to questionnaire-based surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural financing will bring important benefits through optimal production factors, increased agricultural areas, agricultural technologization, and improved production. However, it will also lead to a rise of producers' incomes and the country's GDP (Akdemir et al, 2021). The research conducted by Peng et al (2021) shows that bank loans to farmers and rural enterprises have a substantial constructive effect on agricultural productivity growth and regional and national economic growth.…”
Section: Introductionmentioning
confidence: 99%